Flood Risk Management in a Rural Town in Samborondón, Ecuador: Strategies to Mitigate its Impacts, 2025 - Brambilla Serra, Dino Marcello (2025)
The research is aligned with Sustainable Development Goal 13, which seeks to advocate for action against climate change and improve environmental management to address natural hazards such as flooding caused by intense rainfall. The study aimed to diagnose the vulnerability and impacts of flooding in a rural community, in order to propose practical risk management strategies. A quantitative approach was used, with a non-experimental and cross-sectional design, using a validated questionnaire for a sample of 117 residents. The results show high physical, institutional, economic, and social vulnerability, with significant damage to facilities or equipment, agricultural losses, health problems, and limited response capacity. The community experienced significant social impacts, including temporary migration and emotional distress, with slow recovery due to limited post-disaster preparedness and support. It is concluded that environmental management must be strengthened through investments in infrastructure and community training to reduce latent weaknesses in the face of flood disasters. This review highlights the urgency of comprehensive risk management that includes prevention, mitigation, preparedness, response, and recovery to effectively address this natural threat.